THE APPLICABILITY OF THE GRIPS GEOBAROMETRY IN METAPELITIC ASSEMBLAGES - Wu C.-M.; Zhao G.C. (My University, 2006)
Although the garnet-rutile-ilmenite-plagioclase-silica (quartz) (GRIPS) geobarometer has been experimentally calibrated and widely applied, its applicability to metapelitic rocks has not yet been discussed carefully. In this paper, this barometer was recalibrated by fitting the available reversed-phase equilibrium data incorporating different combinations of activity models of garnet, plagioclase and ilmenite. The resultant GRIPS barometer formalisms reproduce the experimental pressures well within ± 0.2 kbar. The GRIPS and garnet-aluminium silicate-plagioclase-quartz (GASP) barometer values are concordant within ± 1 kbar for pressures above ~ 6 kbar for natural metapelites, but the difference of pressure determinations between these two barometers becomes larger when pressure and/or the grossular content of garnet decrease. However, the pressure difference is independent of ither temperature, or almandine in garnet, or anorthite in plagioclase, or iron content in ilmenite. After testing and application of the GRIPS barometer to aluminosilicate-bearing metapelites and metapelitic assemblages within limited geographical areas as well as within contact thermal aureoles, it is concluded that this barometer may be applied to low- to high-grade, medium- to high-pressure metapelites. The application of the GRIPS barometer to metapelites is not advocated in situations where calcium is deficient in garnet (XCagrt < 0.05) or plagioclase (XCapl < 0.17), or for pressures below ~ 6 kbar. © 2006 Blackwell Publishing Ltd.
Keywords: APPLICABILITY; CALIBRATION; GEOBAROMETER; GRIPS; METAPELITE